Method for preparing a homogeneous mixture of polyolefin solid and liquid additives

By applying acoustic energy to the heterogeneous mixture of polyolefin solids and liquid additives at a frequency of 20 to 100 Hz, the problem of unhomogeneous mixing in the prior art is solved, and homogeneous mixing without the need for melted polyolefin solids is achieved. Reduces the hazards of thermal history and improves the curing and mechanical properties of the mixture.

CN114341234BActive Publication Date: 2025-01-10DOW GLOBAL TECHNOLOGIES LLC
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202080059569.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-29
Filing Date
2020-08-26
Publication Date
2025-01-10
Estimated Expiration
2040-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively mix polyolefin solids and liquid additives without melting polyolefin solids, resulting in poor mixing homogeneity and high thermal history hazard.

Method used

By applying acoustic energy to a heterogeneous mixture containing polyolefin solids and liquid additives at a frequency of 20 to 100 Hz, the temperature is maintained above the freezing point of the liquid additives below the melting temperature of the polyolefin solids, achieving homogeneous mixing without melting Polyolefin solid without mechanical stirring.

Benefits of technology

The homogeneous mixing of polyolefin solids and liquid additives is achieved, reducing the hazards of the thermal process and improving the curing and mechanical properties of the mixture, such as improved tensile strength and elongation of break.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003510445470000251
    Figure BDA0003510445470000251
  • Figure BDA0003510445470000271
    Figure BDA0003510445470000271
  • Figure BDA0003510445470000281
    Figure BDA0003510445470000281
Patent Text Reader

Abstract

A method for forming a homogeneous mixture of a polyolefin solid and a liquid additive without melting the polyolefin solid during the forming. The method comprises applying sonic energy at a frequency of 20 to 100 Hz to a heterogeneous mixture comprising the polyolefin solid and the liquid additive for a period of time sufficient to substantially intermix the polyolefin solid and the liquid additive; and simultaneously maintaining the temperature of the heterogeneous mixture above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming the homogeneous mixture without melting the polyolefin solid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Polyolefins are mixed with additives. Background Art

[0002] Patents and patent application publications in or relating to the art include US 7,188,993 B1; US ​​7695,817 B2; US 8,124,309 B2; US 8,435,714 B2; US 8,680,177 B2; US 8,889,331 B2; US 9,223,236 B2; US 9,593,919 B2; US 9,926,427 B2; US 9,957,360 B2. Non-patent publications in or relating to the art include Assessment of extrusion-sonication process on flame retardant polypropylene by rheological characterization, G. Sanchez-Olivares et al., AIMS Materials Science, 2016; Vol. 3, No. 2, pp. 620-633; and ENHANCED DISPERSION OF PARTICLE ADDITIVE INTO POLYMERS USING TWIN SCREW EXTRUSION WITH ULTRASOUND ASSISTANCE, K. Tarverdi et al., SPE ANTEC Anaheim 2017, pp. 1058-1062.

[0003] Previous compounding methods have relied on mechanically blending the solid (eg, in a stirred tank apparatus) or melt (eg, in a twin screw extruder apparatus) of the polyolefin with the liquid additive. Summary of the invention

[0004] A method for forming a homogenous mixture of a polyolefin solid and a liquid additive without melting the polyolefin solid during the forming is found. The method comprises applying sonic energy at a frequency of 20 to 100 Hz to a heterogeneous mixture comprising a polyolefin solid and a liquid additive for a period of time sufficient to substantially intermix the polyolefin solid and the liquid additive; while maintaining the temperature of the heterogeneous mixture above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming the homogenous mixture without melting the polyolefin solid. DETAILED DESCRIPTION

[0005] A method for forming a homogenous mixture of a polyolefin solid and a liquid additive without melting the polyolefin solid during said forming. The method comprises applying sonic energy to a heterogeneous mixture comprising a polyolefin solid and a liquid additive at a frequency of 20 to 100 Hertz (Hz) for a period of time sufficient to substantially intermix (fully or completely homogenize) the polyolefin solid and the liquid additive together; while maintaining the temperature of the heterogeneous mixture (and optionally, the temperature of a homogeneous mixture formed therefrom) above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming the homogeneous mixture without melting the polyolefin solid. The method may further include the feature of not requiring solidification of the liquid additive. The method may further include the following limitation, wherein during the step of applying sonic energy, the heterogeneous mixture is not mechanically agitated (not mixed by mechanical means).

[0006] Additional aspects of the invention follow; some are numbered below for ease of reference.

[0007] Aspect 1. A method of making a homogenous mixture of a polyolefin solid and a liquid additive without melting the polyolefin solid during said making, the method comprising applying acoustic energy to a first heterogeneous mixture comprising at least one liquid additive and a polyolefin solid at a frequency of 20 to 100 Hz for a period of time and at an acoustic intensity effective to substantially intermix the at least one liquid additive and the polyolefin solid; while maintaining the temperature of the first heterogeneous mixture (and optionally, the temperature of the homogeneous mixture made therefrom) above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby making a first homogeneous mixture comprising the polyolefin solid and the at least one liquid additive without melting the polyolefin solid. The method may include not requiring solidification of the at least one liquid additive. The method may further include the feature of not requiring mechanical movement of the polyolefin solid or the heterogeneous mixture during the applying step. The freezing point of each of the at least one liquid additive is independently less than 20.0°C, alternatively less than 15°C, alternatively less than 5°C. The freezing point of each of the at least one liquid additive may independently be at least -80°C, alternatively at least -50°C, alternatively at least -10°C. The melting temperature of the polyolefin solid (at which melting begins or starts) may be 60°C or higher, alternatively greater than 100°C, alternatively greater than 110°C. The melting temperature of the polyolefin solid (at which melting ends or completes) may be at most 220°C, alternatively at most 180°C, alternatively at most 150°C.

[0008] Aspect 2. The method of aspect 1, wherein the applying step is characterized by any of the following features (i) to (v): (i) the frequency is 50 to 70 Hz, alternatively 55 to 65 Hz, alternatively 58 to 62 Hz, alternatively 59 to 61 Hz; (ii) the time period is 0.5 minutes to 4 hours, alternatively 0.5 minutes to 2 hours, alternatively 1 minute to 60 minutes; (iii) both (i) and (ii); (iv) the first heterogeneous mixture is maintained at a temperature below the melting temperature of the polyolefin solids, including a temperature of 10°C to 109°C, alternatively 15°C to 99°C, alternatively 20.0°C to 39.9°C, alternatively 20.0°C to 29.9°C (e.g., 25°C ± 3°C); and (v) (iv) and any of (i) to (iii). The frequency is set by the acoustic mixer. The intensity is sufficient to move the material with sufficient amplitude to be effective for mixing.

[0009] Aspect 3. The method of aspect 1 or 2, wherein the polyolefin solids of the first heterogeneous mixture are characterized by a physical form (i.e., solid particulate form) of a powder, granules, or pellets, and by a melting temperature of 61°C to 180°C, alternatively 90°C to 180°C, alternatively 110°C to 174°C, alternatively 120°C to 180°C; and at least one liquid additive of the first heterogeneous mixture is characterized by a freezing point of less than 20°C, or by a melting point of 20°C to 99°C; and during the applying step, the first heterogeneous mixture is maintained at a temperature above the freezing point or melting point of the at least one liquid additive and below 110°C. The polyolefin solids of the first heterogeneous mixture may be characterized by an average particle size of 10 to 500 particles per gram (ppg), alternatively 11 to 80 ppg, alternatively 20 to 40 ppg, as measured by counting.

[0010] Aspect 4. The method according to any one of aspects 1 to 3, wherein the polyolefin of the polyolefin solid (i.e., the particulate form of the polyolefin polymer) is: (A) a polyethylene homopolymer; an ethylene / α-olefin copolymer; a (hydrolyzable silane)-functional polyethylene copolymer (HSG-FP copolymer); an ethylene / unsaturated carboxylic acid ester copolymer (e.g., an ethylene / vinyl acetate (EVA) copolymer or an ethylene / (meth) alkyl ester (EAA or EAM) copolymer); or a blend of any two or more thereof. The polyolefin may be a (hydrolyzable silane)-functional polyethylene copolymer (HSG-FP copolymer).

[0011] Aspect 5. The method according to any one of aspects 1 to 4, wherein at least one liquid additive is additive (B) liq to (I) liq Any one or more of: (B) liq , liquid silanol condensation catalyst (dibutyltin dilaurate or ethanesulfonic acid); (C) liq , liquid antioxidant (e.g. 2-methyl-4,6-bis(octylthiomethyl)phenol, e.g. IRGASTAB Cable KV10); (D) liq , liquid colorant (e.g. liquid dye); (E) liq , liquid anti-scorch agent; (F) liq , liquid stabilizers for stabilizing the homogeneous mixture against the action of ultraviolet rays (UV stabilizers), for example liquid hindered amine light stabilizers (HALS); (G) liq , liquid processing aids (e.g., mineral oil); (H) liq , a liquid flame retardant (e.g., brominated polystyrene, brominated rubber, poly(vinyl bromide), poly(vinylidene bromide), poly(brominated alkyl acrylates), poly(brominated alkyl acrylates), or brominated butadiene-styrene copolymers); and (I) liq, which is not a liquid polymer of (A) (e.g., polydimethylsiloxane fluid). (B) liq , the liquid silanol condensation catalyst may be dibutyltin dilaurate or (C1-C4) alkanesulfonic acid. (E) liq The liquid scorch retarder may be 2,4-diphenyl-4-methyl-1-pentene (also known as alpha-methylstyrene dimer or AMSD) or a liquid hydrolyzable silane such as octyltriethoxysilane (OTES) or vinyltrimethoxysilane (VTMS). (E) liq It may be a compound of formula RSi(X)3, wherein R is (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 )alkynyl or X, and each X is independently (C1-C 10 ) alkoxy, (C1-C 10 ) carboxyl, di((C1-C 10 )alkyl)amino or (C1-C 10 )oxime groups. Alternatively or in addition, at least one liquid additive may be a liquid organic peroxide (e.g., t-butyl peroxyacetate), a liquid crosslinking aid (e.g., triallyl isocyanurate), or a liquid moisture generator (e.g., a hydroxyl-terminated polydimethylsiloxane fluid). The homogenous mixture of Aspect 5 is moisture-curable and may comprise 15.00 to 99.99 weight percent (wt %) of (A) HSG-FP copolymer and the remainder being liquid additives, all based on the total weight of the homogenous mixture. In Aspect 5, the polyolefin of the polyolefin solid may be (A) (hydrolyzable silane group)-functional polyethylene copolymer (HSG-FP copolymer).

[0012] Aspect 6. The method of any one of aspects 1 to 5, wherein the first heterogeneous mixture further comprises at least one particulate solid additive other than the polyolefin solid, and the first homogeneous mixture further comprises at least one particulate solid additive. The at least one particulate solid additive may be a solid additive (B). sol to (I) sol Any of: (B) sol , a solid silanol condensation catalyst (e.g., toluenesulfonic acid); (C) sol , a solid antioxidant (e.g., 2,2'-thiobis(6-tert-butyl-4-methylphenol) sold as LOWINOX TBP-6); (D) sol , solid colorant (e.g., carbon black or TiO2); (E) sol , solid scorch retarder (e.g. hydroquinone); (F) sol, solid stabilizers for stabilizing the homogeneous mixture against the action of ultraviolet light (UV stabilizers), for example solid hindered amine light stabilizers (HALS) (for example, poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]), sold as Chimassorb 944); (G) sol , solid processing aids (e.g., N,N'-ethylenebis(stearamide) solids, such as Kemamide W-40); (H) sol , a solid flame retardant (such as a metal hydrate); and (I) sol , a solid polymer other than (A) (e.g., a polypropylene homopolymer or a propylene / ethylene copolymer). Alternatively or in addition, at least one particulate solid additive may be a solid organic peroxide (e.g., dicumyl peroxide), a solid crosslinking aid (e.g., triallyl isocyanurate), or a solid moisture generator (e.g., alumina trihydrate (Al2O3·3H2O) or calcium oxalate monohydrate). The melting temperature (at which melting begins or starts) of each of the at least one particulate solid additive may be greater than 20.0°C, alternatively greater than 100°C, alternatively greater than 200°C. The melting temperature (at which melting ends or completes) of at least one particulate solid additive may be at most 4,000°C, alternatively at most 2,000°C, alternatively at most 1,000°C.

[0013] Aspect 7. The method of any one of aspects 1 to 6, further comprising, before the applying step, forming a first heterogeneous mixture by contacting step (i) or (ii): (i) contacting the polyolefin solid with at least one liquid additive to form a first heterogeneous mixture; or (ii) contacting the polyolefin solid with a lower melting point solid additive having a melting point of 25°C to 110°C (e.g., triallyl cyanurate, melting point 26°C to 28°C) to form a heterogeneous solid premixture, and melting the lower melting point solid additive without melting the polyolefin solid to form the first heterogeneous mixture. The melting point of the lower melting point solid additive may be 30.0°C to 109°C, alternatively 40.0°C to 79.9°C, alternatively 30.0°C to 49.9°C. The polyolefin solid used in the contacting step (i) may not contain at least one liquid additive. The first heterogeneous mixture used in the applying sonic energy step may be freshly prepared. By "fresh" is meant that the time between the contacting step (i) or (ii) and the beginning of the step of applying sonic energy may be sufficiently short so as to prevent the at least one liquid additive from having the time required for passive soaking or absorption (if possible) into the polyolefin solid to any significant degree or any degree. The sufficiently short time between the contacting step and the beginning of the step of applying sonic energy may be less than 30 minutes, alternatively less than 15 minutes, alternatively less than 10 minutes, alternatively less than 5 minutes. Alternatively, the first heterogeneous mixture used in the step of applying sonic energy may be pre-aged. "Pre-aged" means that the time between the contacting step (i) or (ii) and the beginning of the step of applying sonic energy may be sufficiently long so as to allow the at least one liquid additive to have the time required for some but not all of the at least one liquid additive to be passively soaked or absorbed (if possible) into the polyolefin solid to a significant degree or measurable. The sufficiently long time between the contacting step and the beginning of the step of applying sonic energy may be at least 30 minutes, alternatively greater than 60 minutes, alternatively greater than 120 minutes.

[0014] Aspect 8. The method of any one of aspects 1 to 7, further comprising the steps of: contacting the first homogenous mixture with at least one particulate solid additive different from the polyolefin solid to form a second heterogeneous mixture comprising the first homogenous mixture and the at least one particulate solid additive; and subsequently applying sonic energy at a frequency of 20 to 100 Hz and at an intensity effective to substantially intermix the two together, while maintaining the temperature of the second heterogeneous mixture above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming a second homogenous mixture without melting the polyolefin polymer solid during the forming step, the second homogenous mixture comprising the polyolefin solid, the at least one liquid additive and the at least one particulate solid additive. The method may include not requiring solidification of the at least one liquid additive. The at least one particulate solid additive may be as described elsewhere herein.

[0015] Aspect 9. The method of any one of aspects 1 to 8, further comprising the steps of: melting the polyolefin solid of the homogenous mixture to form a molten mixture; shaping the molten mixture to obtain a shaped molten mixture; and cooling the shaped molten mixture to obtain a shaped solid. The shaped solid may be suitable for use as a finished product. Shaping may include coating, extrusion or molding. The homogenous mixture may be the first or second homogenous mixture formed, as indicated in the numbered aspects.

[0016] Aspect 10. The method of aspect 9, wherein the forming step comprises extruding the molten mixture as a coating onto a conductive core (e.g., an electric wire, an optical cable, or both), and curing the coating to produce a coated conductor comprising the conductive core and a coating-formed solid at least partially covering the conductive core. The method may further comprise curing (cross-linking) the coating-formed solid to obtain a coated conductor comprising a conductive core and a coating-formed cured product at least partially covering the conductive core. This aspect can be used to produce a finished product including a power cable such as a low voltage power cable.

[0017] Aspect 11. The method of aspect 9 or 10, further comprising curing the shaped solid polyolefin to obtain a shaped cured product.

[0018] Aspect 12. A shaped cured product prepared by the method of aspect 11.

[0019] The method produces a homogenous mixture in an acoustic mixer device that does not contain components that may interfere with or attenuate the acoustic energy of the applying step. Acoustic mixer devices for use on a variety of scales from laboratory benches to commercial manufacturing are commercially available, including resonant acoustic mixers available from Resodyn Acoustic Mixers, Butte, Montana, USA.

[0020] The method of making a homogeneous mixture is made without melting the polyolefin solid. In a practical sense, homogeneity can be identified by visual inspection of the mixture or sampling (when it changes from a heterogeneous state to a homogeneous state) and measuring the characteristics of the sample. For example, homogeneity is achieved when the sampling error of the measurement is negligible or the same as the total error of the measurement. Under all other conditions being equal, (i) the greater the acoustic energy, the shorter the period required to achieve homogeneity, and vice versa; and (ii) the closer the frequency resonating with the polymer solid, the shorter the period required to achieve homogeneity, and vice versa.

[0021] The homogeneous mixture made by the method can be characterized as homogeneous because the liquid additive is substantially uniformly adsorbed as a film on the outer surface of the polyolefin solid and any accessible inner surface. "Substantially uniform adsorption" means that almost all accessible surfaces of the polyolefin polymer solid have at least some liquid additive adsorbed thereon, although the amount of adsorbed liquid additive may vary on the surface. After adsorption on the surface of the polyolefin solid, the liquid additive may remain thereon, or at least some may be immersed or absorbed or migrated into the polyolefin solid to make an immersed polyolefin solid containing at least some liquid additive under the surface. In embodiments where some or all of the liquid additive has been immersed or absorbed or migrated into the polyolefin solid, the surface of the polyolefin solid may appear semi-dry or dry (free of liquid additive), but the total weight of the polyolefin solid immersed in the liquid additive will be equal to the weight of the heterogeneous mixture to make the homogeneous mixture.

[0022] The method enables the preparation of a homogenous mixture comprising a polyolefin solid and at least one liquid additive without the use of melt extrusion or melt compounding (which requires molten polyolefin solids). Thus, the thermal history of the homogenous mixture prepared by the method is less harmful (e.g., less oxidative degradation and / or less scorch or premature crosslinking) than the thermal history of a comparative homogenous mixture prepared by melt extrusion or melt compounding. For example, the homogenous mixture prepared by the method may have improved curing characteristics (e.g., lower thermal creep %), improved mechanical properties (e.g., higher tensile strength, greater elongation at break) before and / or after heat aging thereof.

[0023] Liquid refers to an amorphous substance intermediate between a gas and a solid and having a stable volume, but no defined shape.

[0024] Melting means changing a material from a solid substance to a liquid substance. Typically, melting means that the change is complete so that the liquid substance does not contain unmelted solid form of the material. The temperature of the material characterizing a material as solid or liquid is 20°C.

[0025] Polyolefin means any macromolecule comprising constitutional units derived from polymerizing olefin functional monomers or copolymerizing at least two olefin functional monomers, or a mixture of such macromolecules. The polyolefin may be amorphous (i.e., having a glass transition temperature but no melting point in differential scanning calorimetry (DSC)) or semi-crystalline (i.e., having a glass transition temperature and a melting point in DSC).

[0026] Examples of suitable polyolefins are ethylene-based polymers such as polyethylene homopolymers and ethylene-based copolymers; propylene-based polymers such as polypropylene homopolymers and propylene-based copolymers; halogenated polyolefins; grafted alkenyl-functional monocyclic organosiloxane-polyethylene copolymers; ethylene / alkenyl-functional monocyclic organosiloxane copolymers; and polystyrene polymers such as those given in US 2012 / 0209056 A1. Examples of halogenated polyolefins are poly(vinyl chloride) polymers (PVC), chlorinated poly(vinyl chloride) polymers (CPVC), chlorinated polyethylene polymers, chlorinated natural or synthetic rubbers, chlorinated polystyrenes, poly(vinyl bromide) polymers, brominated butadiene / styrene copolymers, brominated polystyrene polymers, brominated natural or synthetic rubbers, and copolymers of vinyl chloride and copolymerizable ethylenically unsaturated monomers. Examples of copolymerizable ethylenically unsaturated monomers are vinyl acetate, vinyl butyrate, vinyl benzoate, vinylidene chloride, alkyl fumarate, alkyl maleate, vinyl propionate, alkyl acrylate, alkyl methacrylate, α-methyl chloroacrylate, styrene, trichloroethylene, vinyl ether, vinyl ketone, 1-fluoro-2-chloroethylene, acrylonitrile, chloroacrylonitrile, allylene diacetate and allylene diacetate, and mixtures of any two or more thereof. For details, see US 10,119,015 B2. The polyolefin may be a thermoplastic elastomer or a compatibilizer, such as those given in US 8,697,787 B2. The polyolefin that is a copolymer may be a dimer (made by polymerizing two different olefin monomers), a terpolymer (made by polymerizing three different olefin monomers) or a tetrapolymer (made by polymerizing four different olefin monomers). The polyolefin that is a copolymer may be a block copolymer or a random copolymer.

[0027] In some aspects, the polyolefin is an ethylene-based polymer. Examples of suitable ethylene-based polymers are polyethylene homopolymers, ethylene / (C4-C 20)α-olefin copolymers, ethylene / propylene copolymers, ethylene / propylene / diene monomer (EPDM) copolymers, such as ethylene / propylene / 1,3-butadiene terpolymers and ethylene / 1-butene / styrene copolymers. Suitable ethylene / (C4-C 20 Examples of α-olefin copolymers are ethylene / 1-butene copolymers, ethylene / 1-hexene copolymers, and ethylene / 1-octene copolymers. Ethylene-based polymers may be ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), or ultra high density polyethylene (UHDPE). Many ethylene-based polymers are sold by The Dow Chemical Company under trade names such as AFFINITY, ATTANE, DOWLEX, ENGAGE, FLEXOMER, or INFUSE. Other ethylene-based polymers are sold by other suppliers under trade names such as TAFMER, EXCEED, and EXACT.

[0028] A monomer-based polymer such as an "ethylene-based polymer" or a "propylene-based polymer" means a macromolecule comprising 51 to 100 weight percent (wt%) of constitutional units derived from a monomer (e.g., ethylene or propylene) and 0 to 49 wt% of constitutional units derived from one or more comonomers other than the monomer.

[0029] An olefin functional monomer is an organic molecule containing at least one polymerizable carbon-carbon double bond, wherein the organic molecule is composed of carbon atoms, hydrogen atoms, optionally at least one halogen atom and optionally at least one heteroatom selected from N, O, S, Si or P. Typically, the at least one heteroatom comprises an oxygen atom and / or a silicon atom. Examples of olefin functional monomers are ethylene, propylene, (C4-C 20 )α-olefins, 1,3-butadiene, norbornene, 5-ethylidene-2-norbornene, vinyl fluoride, vinyl chloride, vinyl bromide, vinyl iodide, vinyl acetate, (C1-C6) alkyl acrylates, (C1-C6) alkyl methacrylates, vinyltrialkoxysilanes, such as vinyltrimethoxysilane of the formula H2C=C(H)Si(OCH3)3, or alkenyl-functional monocyclic organosiloxanes, such as 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, "(D Vi )3" (CAS No. 3901-77-7) or 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, "(D Vi )4” (CAS No. 2554-06-5).

[0030] Solid refers to a state of matter with a stable volume and a defined shape. It can be amorphous, crystalline or semi-crystalline.

[0031] Solidification means changing a material from a liquid substance to a solid substance. Typically, solidification means that the change is complete so that the solid substance does not contain an unsolidified form of the material.

[0032] Without being bound by theory, it is believed that applying acoustic energy at a frequency of 20 to 100 Hz produces sound waves that cause rapid oscillations of polyolefin solids. It undergoes relatively large entity displacements, and it is believed that its magnitude and rapidity depend on frequency and sound intensity. The oscillation of this polyolefin solid causes it to intermix rapidly with at least one liquid additive to form a first homogeneous mixture. Therefore, without the need to solidify at least one liquid additive, and optionally without the need to mechanically mix polyolefin solids and at least one liquid additive, and without the need to solidify at least one liquid additive or melt polyolefin solids, make the first homogeneous mixture. The inventive method is different from previous mixing methods, which rely on mechanical blending of a solid (e.g., in a stirred tank device) or melt (e.g., in a twin-screw extruder device) of a polyolefin with a liquid additive.

[0033] Sounds with frequencies less than 20 Hertz (Hz) are referred to as "infrasound"; and 20 Hz to 20 kilohertz (KHz), are referred to as "sound"; and greater than 20 KHz (up to 200 megahertz (MHz) or higher), are referred to as "ultrasound". Without being bound by theory, it is believed that infrasound and ultrasound and sound above 100 Hz are not able to rapidly vibrate the polyolefin solids in a heterogeneous mixture in a manner that would produce relatively large physical displacements thereof and thus produce a homogeneous mixture. Acoustic energy applied at a frequency of 20 to 100 Hz is referred to herein as "acoustic mixing".

[0034] The method may further include the feature that no mechanical movement of the polyolefin solid or heterogeneous mixture is required during the applying step. Mechanical movement means movement by applying direct contact force manually or via a machine, wherein a physical object (e.g., a stirring paddle, a screw, a plunger, or an admixture) contacts and thus moves the material. Examples of mechanical movement are stirring, screw mixing, plunger mixing, admixture mixing, and other direct physical contact. Contact forces do not include electromagnetic forces, gravity, acoustic forces, and convection forces.

[0035] The method may further include the feature of substantially or completely eliminating the need for immersing (or absorbing) the liquid additive into the polyolefin solid during the applying step. Immersing requires the miscibility of the liquid additive in the polyolefin solid and effective immersion conditions. Such immersion conditions include a sufficient period of time (e.g., 8 to 16 hours) and a sufficient temperature from ambient temperature (e.g., 20° C.) to elevated temperatures (e.g., 60° C. to 90° C.) to allow the liquid additive to migrate into the polyolefin solid.

[0036] The expression "heterogeneous mixture" may refer to a first or second heterogeneous mixture of a numbered aspect or claim or a heterogeneous mixture of an unnumbered aspect, as the case may be.

[0037] Heterogeneous mixtures. May be made by contacting a pure polyolefin solid without a liquid additive with a liquid additive without homogenizing it. Alternatively, may be made by contacting a homogenous mixture with a second liquid additive and / or a particulate solid additive without homogenizing it, the homogenous mixture being made by sonic mixing or comparative melt mixing of the present invention. Alternatively, may be made by dehomogenizing a homogenous mixture of a polyolefin solid and a liquid additive, such as by allowing the homogenous mixture to stand at 25°C for a period sufficient to allow some of the liquid additive to coalesce, or to allow the liquid additive to migrate to the surface of the polyolefin solid. Alternatively, may be made by heating a heterogeneous mixture of a polyolefin solid and a lower melting point solid additive having a melting temperature lower than the melting temperature of the polyolefin solid, the heating being heated to a temperature greater than the melting temperature of the lower melting point solid additive but less than the melting temperature of the polyolefin solid, and for a period sufficient to melt at least some, alternatively all, of the lower melting point solid additive.

[0038] As described above, a heterogeneous mixture may have never been homogenized or may have been dehomogenized. In either case, a heterogeneous mixture is a non-uniform, physical combination of matter, for example consisting of unblended or partially (incompletely) blended components. Homogenization of a dehomogenized mixture can restore its predecessor, a homogenous mixture, without the need to re-melt the polyolefin.

[0039] Polyolefin solids. A polymer macromolecule in the form of a finely divided, solid material (i.e., solid particulates) independently comprising at least 5, alternatively 10 to 200,000 constituent units derived from polymerizing one or more olefin functional monomers. Examples of olefin functional monomers are ethylene, α-olefins, dienes, unsaturated carboxylic acid esters, and olefin functional hydrolyzable silanes. The polyolefin of the polyolefin solids may be an ethylene-based polymer comprising: 51 to 100 wt% of vinyl units derived from polymerized ethylene and 49 to 0 wt% of comonomer units derived from polymerized ketones, alternatively two olefin functional monomers (comonomers) selected from: propylene; (C4-C8) α-olefins, such as 1-butene, 1-hexene or 1-octene; unsaturated carboxylic acid esters and olefin functional hydrolyzable silanes. Alternatively, the polyolefin of the polyolefin solid may be a propylene-based polymer comprising 51 to 100 wt% of propylene units derived from polymerized propylene and 49 to 0 wt% of comonomer units derived from polymerized ketones, alternatively two olefin functional monomers (comonomers) selected from the group consisting of ethylene, (C4-C8) α-olefins such as 1-butene, 1-hexene or 1-octene; unsaturated carboxylic acid esters and olefin functional hydrolyzable silanes. Examples of α-olefins are propylene; (C4-C8) α-olefins such as 1-butene, 1-hexene or 1-octene; and (C 10 -C 20 )α-olefins. An example of a diene is 1,3-butadiene. Examples of unsaturated carboxylates are alkyl acrylates, alkyl methacrylates and vinyl carboxylates (e.g. vinyl acetate). Examples of olefin-functional hydrolyzable silanes are vinyltrialkoxysilanes, vinyltri(dialkylamino)silanes and vinyl(trioximino)silanes. Examples of polyolefins of the polyolefin solids are polyethylene homopolymers, polypropylene homopolymers, ethylene / propylene copolymers, ethylene / (C4-C8)α-olefin copolymers, ethylene / propylene / 1,3-butadiene copolymers, ethylene / unsaturated carboxylic acid ester copolymers and ethylene / vinyl-functional hydrolyzable silane copolymers.

[0040] The polyolefin polymer solid may be porous or non-porous.The polyolefin polymer solid may comprise a powder, granules or pellets.

[0041] Liquid additive. A pure liquid or a solution of a liquid or solid additive (solute) is dissolved in a liquid solvent. The pure liquid consists of molecules that are not polyolefin polymer macromolecules and have temperature characteristics (i) or (ii): (i) a freezing point below 0°C, alternatively 0°C to 20.0°C; or (ii) a melting point of 20.1°C to 99°C, alternatively 30.0°C to 79.9°C, alternatively 40.0°C to 69.9°C. The liquid additive solute in the solution may be the same compound as described for the pure liquid. The solid additive solute in the solution may be a compound having a solubility of at least 1% by weight in the liquid solvent. The liquid solvent may be an organic liquid selected for a boiling point higher than the temperature of the heterogeneous mixture during the application step. Suitable liquid solvents are hydrocarbons (e.g., mineral oil or xylene), ethers (e.g., dibutyl ether), and blends of two or more thereof. In some aspects, the liquid additive is added to the polyolefin solid in pure liquid form and the heterogeneous mixture does not contain any liquid solvent.

[0042] The term "liquid additive" is used to describe the material state of the additive at the temperature of the heterogeneous mixture during the step of applying sonic energy, and does not necessarily require that the additive be liquid at ambient temperature (e.g., 23° C.) if the temperature of the heterogeneous mixture during the step of applying is greater than ambient temperature. In some aspects, the liquid additive is liquid at ambient temperature (e.g., at 23° C.).

[0043] The liquid additive may or may not impart at least one beneficial functional property to the homogenous mixture and / or its polyolefin solids. For example, the liquid additive may be a filler material that is merely used to reduce the cost of a product made from the homogenous mixture, but does not need to provide a functional benefit thereto, relative to the cost of a product made from the polyolefin solids without the liquid additive. Alternatively, the liquid additive may impart at least one functional property to the homogenous mixture and / or its polyolefin solids, such as color, improved stability (e.g., degradation, embrittlement, sagging, or dielectric loss effects caused by exposure to heat, ultraviolet light, electricity, and / or water), a crosslinking source (when the liquid additive is a crosslinking aid or catalyst for enhancing crosslinking of the polyolefin), improved conductivity (e.g., electrical and / or thermal conductivity), and increased modulus.

[0044] Each heterogeneous mixture and the homogeneous mixture independently may contain only one liquid additive, alternatively a combination of two or more different liquid additives.

[0045] The heterogeneous mixture and thus the homogeneous mixture produced therefrom by the method may be free of (i.e., may lack) particulate solid additives. In these embodiments, the heterogeneous mixture and thus the homogeneous mixture produced therefrom by the method may consist essentially of polyolefin solids and at least one liquid additive, alternatively consist of polyolefin solids and at least one liquid additive.

[0046] Alternatively, the heterogeneous mixture and thus the homogeneous mixture produced therefrom by the method may further comprise a particulate solid additive other than the polyolefin solid. In these embodiments, the heterogeneous mixture and thus the homogeneous mixture produced therefrom by the method may consist essentially of, alternatively consist of, the polyolefin solid, at least one such liquid additive and at least one such particulate solid additive.

[0047] Optional particulate solid additive. A substance that is not or does not contain a polyolefin polymer, that is, a polymer that is not any type of polymer or a polymer in which the constituent units are not derived from olefin functional monomers. The characteristics of the particulate solid additive can be characterized by a glass transition temperature (if present) and / or a melting temperature greater than the melting temperature of the polyolefin solid (for example, a melting temperature greater than 140°C, alternatively greater than 180°C). The actual glass transition temperature (if present) and melting temperature of the particulate solid additive are not important, as long as they are high enough so that the particulate solid additive does not glass transition or melt during the application step. The heterogeneous mixture and the homogeneous mixture may contain zero particulate solid additives, alternatively one particulate solid additive, alternatively a combination of two or more different particulate solid additives. The particulate solid additive may be inorganic or organic. Examples are carbon black, carbon nanotubes, diamond powder, graphite, graphene, powdered metal, powdered metal oxide, solid flame retardant, silica, alumina and silicate glass beads. In some aspects, the heterogeneous mixture, the method of making and the homogeneous mixture made therefrom do not contain particulate solid additives.

[0048] The polyolefin of the polyolefin solid may be a (A) HSG-FP copolymer. The (A) HSG-FP copolymer is made from comonomers comprising ethylene and optional olefin functional comonomers, wherein at least one olefin functional comonomer is an olefin functional hydrolyzable silane. The composition of the (A) HSG-FP copolymer may be characterized by constituent units selected from the following: ethylene units, alkylene-hydrolyzable silane units, optional propylene units, and optional comonomer units derived from optional olefin comonomers. Optionally, 0, 1 or more olefin comonomers may be selected from (C4-C 20)α-olefins, olefin unsaturated carboxylic acids, olefin unsaturated carboxylic acid esters, olefin unsaturated carboxylic acid anhydrides and combinations thereof. The carboxylic acid may be a monocarboxylic acid or a dicarboxylic acid. The carboxylic acid ester may be a monocarboxylic acid ester, a dicarboxylic acid monoester or a dicarboxylic acid diester. The olefin-unsaturated carboxylic acid may be a terminal unsaturated (C2-C8) carboxylic acid, alternatively (meth) acrylic acid, alternatively an unsaturated dicarboxylic acid. The olefin unsaturated carboxylic acid ester may be a (C2-C8) carboxylic acid vinyl ester; alternatively, a (C2-C5) carboxylic acid vinyl ester (e.g., vinyl acetate, vinyl propionate or vinyl butyrate); alternatively, a (meth) acrylic acid (C1-C8) alkyl ester; alternatively, a (meth) acrylic acid (C1-C3) alkyl ester; alternatively, a di(C1-C8) alkyl diester of an unsaturated dicarboxylic acid; alternatively, a mono(C1-C8) alkyl ester of an unsaturated dicarboxylic acid; alternatively, a mono(C1-C8) alkyl ester of maleic acid. (Meth)acrylate means H2C=CHCO2- or H2C=C(CH3)CO2-. The CTA may be acetone, methyl ethyl ketone, propionaldehyde, 2-propanol, ethyl acetate, isobutylene, butane, 2-methylpropane, ISOPARTM-C, ISOPARTM-E, ISOPARTM-H or a combination of any two or more thereof. The CTA may be present in an amount of 0.03 to 10 wt% of the polymerization reaction mixture.

[0049] The (A) HSG-FP copolymer may be characterized by a total hydrolyzable silane content of 0.43 to 0.99 mol%. The total mol% of the hydrolyzable silane content is calculated from the wt% value of the hydrolyzable silane content, wherein the wt% value is determined according to the X-ray fluorescence (XRF) test method described later. For example, when the at least one alkenyl functional hydrolyzable silane is vinyl trimethoxy silane (VTMS), which has a molecular weight of 148.23 g / mol, and the comonomer content is 2.0 wt%, mol% = 0.38 mol%. When the VTMS comonomer content is 5.0 wt%, mol% = 0.99 mol%. The mol% hydrolyzable silane content at any given wt% hydrolyzable silane content value will vary inversely with the molecular weight of the at least one alkenyl functional hydrolyzable silane from which the hydrolyzable silane groups are derived.

[0050] (A) The HSG-FP copolymer contains hydrolyzable silane groups. These groups can be independently of the formula (R 2 ) m (R 3 ) 3-m Si-monovalent group, wherein the subscript m is an integer of 1, 2 or 3; each R 2are independently H, HO-, (C1-C8)alkoxy, (C2-C6)carboxyl, phenoxy, (C1-C6)alkyl-phenoxy, (C1-C6)alkyl(H)N-, ((C1-C6)alkyl)2N-, (C1-C6)alkyl(H)C=NO- or ((C1-C6)alkyl)2C=NO-; and each R 3 are independently (C1-C8) alkyl or phenyl. 2 It may be free of H and HO-, and alternatively free of phenoxy and (C1-C6) alkyl-phenoxy. 2 It may independently be (C1-C6)alkoxy, (C2-C6)carboxyl, ((C1-C6)alkyl)2N-, (C1-C6)alkyl(H)C=NO- or ((C1-C6)alkyl)2C=NO-; alternatively (C1-C6)alkoxy; alternatively (C2-C6)carboxyl; alternatively ((C1-C6)alkyl)2N-; alternatively (C1-C6)alkyl(H)C=NO-; alternatively ((C1-C6)alkyl)2C=NO-. All the hydrolyzable silyl groups of the (A)HSG-FP copolymer may be the same. The hydrolyzable silyl groups are derived from the hydrolyzable silane groups of at least one alkenyl-functional hydrolyzable silane (comonomer), and the comonomer units of the (A)HSG-FP copolymer containing such groups are prepared therefrom.

[0051] Optional additives (B) silanol condensation catalyst. (B) can be selected from any one of (i) to (iv): (i) Bronsted acid ( acid); (ii) a Bronsted base; (iii) a Lewis acid; and (iv) a Lewis base. (B) may be (i) or (iii); alternatively (ii) or (iv). (B) may be a Lewis acid, which may be a dialkyltin diformate. (B) may be a Bronsted acid, which may be a sulfonic acid of the formula RSO3H, wherein R is (C1-C 10 ) alkyl, (C6-C 10 ) aryl, hydrocarbon (C1-C 10 ) alkyl substituted (C6-C 10 ) aryl or hydrocarbon (C6-C 10 ) aryl substituted (C1-C 10 ) alkyl; or a blocked sulfonic acid, which forms the sulfonic acid in situ.

[0052] Optional Additives (C) Antioxidant: An organic molecule that inhibits oxidation, or a collection of such molecules. The (C) antioxidant is different in composition from the (F) stabilizer, which means that when the heterogeneous or homogeneous mixture contains both (C) and (F), the compound used as (C) is different from the compound used as (F). The (C) antioxidant is used to provide antioxidant properties to the heterogeneous or homogeneous mixture and / or the cured polymer product made by curing the homogeneous mixture. Examples of suitable (C) are bis(4-(1-methyl-1-phenylethyl)phenyl)amine (e.g. NAUGARD 445); 2,2'-methylene-bis(4-methyl-6-tert-butylphenol) (e.g. VANOX MBPC); 2,2'-thiobis(2-tert-butyl-5-methylphenol (CAS No. 90-66-4; 4,4'-thiobis(2-tert-butyl-5-methylphenol) (also known as 4,4'-thiobis(6-tert-butyl-m-cresol), CAS No. 96-69-5, commercially available as LOWINOX TBM-6); 2,2'-thiobis(6-tert-butyl-4-methylphenol (CAS No. 90-66-4, commercially available as LOWINOX TBP-6); tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione (e.g. CYANOX 1790); pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate (e.g. IRGANOX 1010, CAS No. 6683-19-8); 2,2'-dithiodiethylenediyl 3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate (e.g. IRGANOX 1035, CAS No. 41484-35-9); distearyl thiodipropionate ("DSTDP"); dilauryl thiodipropionate (e.g. IRGANOX PS 800); stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (e.g. IRGANOX 1076); 2,4-bis(dodecylthiomethyl)-6-methylphenol (IRGANOX 1726); 4,6-bis(octylthiomethyl)-o-cresol (e.g., IRGANOX 1520); and 2',3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionohydrazide (IRGANOX 1024). (C) may be 4,4'-thiobis(2-tert-butyl-5-methylphenol) (also known as 4,4'-thiobis(6-tert-butyl-m-cresol); 2,2'-thiobis(6-tert-butyl-4-methylphenol; tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione; distearyl thiodipropionate; or dilauryl thiodipropionate; or any combination of two or more thereof.The combination may be tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione and distearyl thiodipropionate. The heterogeneous and / or homogeneous mixture may be free of (C). When present, (C) antioxidant may be 0.01 to 1.5 wt%, alternatively 0.1 to 1.0 wt%, of the total weight of the heterogeneous and / or homogeneous mixture.

[0053] Optional additive (D) colorant. For example, a pigment or dye. For example, carbon black or titanium dioxide. Carbon black can be provided as a carbon black masterbatch, which is a blend of poly (1-butene-co-ethylene) copolymer (≥95wt% to <100wt% of the total weight of the masterbatch) and carbon black (>0wt% to ≤5wt% of the total weight of the masterbatch). Carbon black is a finely divided form of homocrystalline carbon with a high surface area: volume ratio, but lower than the surface area: volume ratio of activated carbon. Examples of carbon black are furnace black, acetylene black, conductive carbon (e.g., carbon fiber, carbon nanotubes, graphene, graphite, and expanded graphite flakes). The heterogeneous and / or homogeneous mixture may be free of (D). When present, (D) may be 0.1 to 35wt% of the heterogeneous and / or homogeneous mixture, alternatively 1 to 10wt%.

[0054] Optional Additives (E) Scorch Retardants. (E) Scorch retarders are used to inhibit premature moisture curing of moisture-curable embodiments of heterogeneous and / or homogeneous mixtures, where premature moisture curing would result from premature or prolonged exposure of the mixture to ambient air or when the mixture is at ambient or elevated temperatures (e.g., during subsequent melt extrusion). Examples of (E) are octyltriethoxysilane and octyltrimethoxysilane and vinyltrimethoxysilane. The heterogeneous and / or homogeneous mixture may be free of (E). If present, (E) may be 0.001 to 5.0 wt %, alternatively 0.01 to 3.0 wt %, alternatively 0.10 to 1.5 wt %, alternatively 0.15 to 1.0 wt % of the heterogeneous and / or homogeneous mixture.

[0055] The optional additive (F) is a stabilizer for stabilizing heterogeneous and / or homogeneous mixtures against ultraviolet light (UV stabilizer). The composition of the (F) stabilizer is different from the (C) antioxidant, which means that when the mixture contains both (C) and (F), the compound used as (C) is different from the compound used as (F). Examples are hindered amine light stabilizers (HALS), benzophenones or benzotriazoles. The (F) UV stabilizer can be a molecule containing a basic nitrogen atom bonded to at least one sterically bulky organic group and acting as an inhibitor of degradation or decomposition, or a collection of such molecules. HALS are compounds having sterically hindered amino functional groups and inhibiting oxidative degradation and can also increase the shelf life of embodiments of the mixture containing organic peroxides. Examples of suitable (F) are dimethyl succinate, polymers with 4-hydroxy-2,2,6,6-tetramethyl-1-piperidin-ethanol (CAS No. 65447-77-0, commercially available as LOWILITE 62); and N,N'-bisformyl-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexanediamine (CAS No. 124172-53-8, commercially available as Uvinul 4050H). The heterogeneous and / or homogeneous mixture may be free of (F). If present, the (F) UV stabilizer may be 0.001 to 1.5 wt %, alternatively 0.002 to 1.0 wt %, alternatively 0.05 to 0.1 wt % of the heterogeneous and / or homogeneous mixture.

[0056] Optional Additives (G) Processing Aids: Molecules that reduce the stickiness of the polymer melt in manufacturing equipment (such as extruders and molds) and, in embodiments where the homogeneous mixture is subsequently used, reduce the melt fracture of the material. (G) may be fluoropolymers, polyorganosiloxanes, metal salts of fatty carboxylic acids, fatty formamides, waxes, ethylene oxide (co)polymers, and nonionic surfactants. The heterogeneous and / or homogeneous mixture may be free of (G). When present, (G) processing aids may be 0.05 to 5 wt% of the heterogeneous and / or homogeneous mixture.

[0057] Optional additives (H) flame retardant. (H) Flame retardant is a compound that inhibits or delays the spread of fire by inhibiting chemical reactions in flames. (H) Flame retardant may be: (H1) minerals, (H2) organic halogen compounds, (H3) (organic) phosphorus compounds; (H4) halogenated silicones; (H5) any two or more combinations of (H1) to (H4); (H6) any one of (H1) to (H4) and a flame retardant synergist (e.g., antimony dioxide). The heterogeneous and / or homogeneous mixture may be free of (H). When present, (H) flame retardant may be 0.1 to 80.0 wt %, alternatively 1 to 50.0 wt %; and alternatively 5 to 30.0 wt % of the heterogeneous and / or homogeneous mixture.

[0058] The heterogeneous and / or homogeneous mixture may further comprise (I), a polymer other than (A) or a styrenic polymer (which is not (A)). The polymer (I) other than (A) may be a polyolefin-based macromolecule having a different composition from that of the polymer (A). The polymer (I) other than (A) may be a polyolefin, a styrenic polymer, a rubber, a poly(vinyl chloride) polymer, a polyorganosiloxane (such as polydimethylsiloxane (PDMS)), or a blend of any two or more thereof.

[0059] Finished article. A finished article made from the homogenous mixture may comprise a shaped form thereof. Examples are coatings on substrates, tapes, films, laminate layers, foams and pipes.

[0060] Coated conductor. The finished product may be a coated conductor comprising a conductive core and a polymeric layer at least partially surrounding the conductive core, wherein at least a portion of the polymeric layer comprises a homogenous mixture, or a cured polymer product cured thereof. The entire polymeric layer may comprise a cured polymer product. The conductive core may be a linear shape (e.g., like a wire) having a certain length and a proximal end and a distal end spaced apart from each other by the length of the linear shape; and the polymeric layer may surround the conductive core except for the proximal end and the distal end. The coated conductor may further comprise one or more additional polymeric layers, which independently may or may not comprise a cured polymer product; and / or an outer shielding layer (e.g., a metal sheath or casing). The coated conductor may comprise one or two insulating layers, at least one of which comprises a cured polymer product; alternatively or additionally, one or two semiconductive layers, at least one of which comprises a cured polymer product containing carbon black; alternatively or additionally, an outer shielding layer, which comprises a cured polymer product.

[0061] Moisture-curable embodiments comprising a homogenous mixture of (A) HSG-FP copolymers can be moisture cured by exposure to ambient air or by immersion in hot water at 70 to 95° C. to produce a cured polymer product. The degree of crosslinking of the cured polymer product can be characterized by measuring the percent thermal creep.

[0062] Substitution: Any, all but one or each functional group may be unsubstituted.

[0063] Alternative takes precedence over different embodiments. Choices may be provided, but are not required. Optional (optionally): not present (or excluded), present (or included) instead.

[0064] Examples

[0065] Melt index ("I2"): measured according to ASTM D1238-13 using the 190°C / 2.16kg condition (formerly referred to as "Condition E"). The unit is grams per 10 minutes (g / 10 min).

[0066] The weight percentage (wt%) of silicon atom (Si) content in (A) HSG-FP copolymer test samples was determined using XRF spectroscopy, and the hydrolyzable silane comonomer unit wt% was then calculated. A Buehler SimpliMet 300 automatic mounting press was used, which was preheated for 3 minutes at 115.6°C (240 degrees Fahrenheit (℉)), and the test sample in powder form was pressed for 1 minute at 8.3 megapascals (MPa; 1,200 pounds per square inch (psi)) to form a thin plate with a thickness of about 6 mm, and the thin plate was cooled to 25°C. The Si atom content of the thin plate was analyzed by wavelength dispersive XRF using a wavelength dispersive X-ray fluorescence spectrometer from PANalytical Axios. The Si atom content was determined by comparing the line intensity in its XRF spectrum with a calibration curve of Si atom content established using a polymer standard with a known Si atom concentration, as measured independently using neutron activation analysis (NAA) or inductively coupled plasma (ICP) methods. The Si atom wt% value measured by XRF and the molecular weight of the at least one alkenyl functional hydrolyzable silane comonomer from which the hydrolyzable silane groups are derived are used to calculate the wt% of hydrolyzable silane comonomer units (i.e., the wt% of hydrolyzable silane groups) in the (A) HSG-FP copolymer. For the hydrolyzable silane groups derived from vinyltrimethoxysilane (VTMS), a VTMS molecular weight of 148.23 g / mol is used. To calculate the hydrolyzable silane content (wt% of hydrolyzable silane comonomer units) in (A) HSG-FP copolymer, the Si atom wt% ("C") obtained by XRF and the following formula are used: p = C*(m / 28.086) (1 / 10000 ppmw), where * means multiplication, / means division, p is the wt% hydrolyzable silane groups in (A), C is the Si atomic weight (XFR) (in parts per million by weight, ppmw), m is the molecular weight (in g / mol) of at least one alkenyl-functional hydrolyzable silane comonomer from which the hydrolyzable silane groups are derived, 28.086 is the atomic weight of the silicon atom, and 10000 ppmw is the amount in parts per million by weight of 1.00 wt%. For example, when XRF shows 379 ppmw of Si atoms in (A) HSG-FP copolymer and the comonomer used to make (A) is VTMS with a molecular weight of 148.23 g / mol, the wt% comonomer content is 0.20 wt%.To calculate the mol% of hydrolyzable silane comonomer units in the (A) HSG-FP copolymer using at least one alkenyl-functional hydrolyzable silane comonomer, the calculated wt% of the hydrolyzable silane comonomer units in (A) and the following equation are used: G = 100*(p / m) / [(p / m)+(100.00wt%-p) / 28.05g / mol], where * means multiplication, G is the molar percentage (mol%) of the hydrolyzable silane groups in (A); p is the wt% of the hydrolyzable silane groups in (A), m is the molecular weight (in g / mol) of the at least one alkenyl-functional hydrolyzable silane comonomer from which the hydrolyzable silane groups are derived, and 28.05 g / mol is the molecular weight of monomer ethylene (H2C=CH2). For example, when the comonomer content is 2.0 wt% and the comonomer is VTMS, p = 2.0 wt% and m = 148.23 g / mol and G = 0.38 mol%. When the comonomer content is 5.0 wt% and the comonomer is VTMS, p = 5.0 wt% and m = 148.23 g / mol and G = 0.99 mol%. When two or more alkenyl functional hydrolyzable silane comonomers having different molecular weights are used to make (A), the molecular weight used to calculate the total mol% of all hydrolyzable silane groups in (A) is the weighted average molecular weight of the comonomers. The weighing can be determined by the ratio of the amounts of comonomers fed into the GPP reactor; alternatively by NMR spectroscopy of the (A) HSG-FP copolymer to determine the relative amounts of different comonomer units in the (A) HSG-FP copolymer when the corresponding hydrolyzable silyl groups are bonded to different types of carbon atoms (e.g., tertiary versus secondary carbon atoms); alternatively by Fourier transform infrared (FT-IR) spectroscopy, calibrated to provide quantification of different types of comonomers.

[0067] Tape Preparation Method: Moisture-curable polyethylene formulations were used to prepare tapes for ambient cure and thermal creep test evaluation. The formulations prepared according to the above method were fed into a Brabender 1.905 cm (3 / 4 inch) extruder equipped with a 25:1 dual mixing zone (pineapple) screw, a 40 / 60 / 40 mesh screen package, and a 5.08 cm (2 inch) wide head die. The extruder had a temperature profile in four zones at 150°C, 160°C, 170°C, and 170°C at the head die and a screw speed of 60 revolutions per minute (rpm). This produced different formulations in the form of tapes with an average thickness of 1.37 to 1.70 mm (54 to 67 mils).

[0068] Ambient Moisture Cure Method. For characterization and comparison, ambient cure conditions were controlled as follows. The tape samples made by the tape preparation method were cured at 23°C. ±2°C and 50% ±2% RH environment for up to 182 days to make a cured polymer product as indicated in Tables 3 to 5. The thermal creep of the cured polymer product was measured according to the Thermal Creep Test Method.

[0069] Hot Water Curing Method. The tape samples made by the tape preparation method were immersed in a 90°C ± 2°C water bath for 20 hours, followed by a cured polymer product as indicated in Tables 3 to 5. The thermal creep of the cured polymer product was measured according to the Thermal Creep Test Method.

[0070] Thermal creep test method. The degree of crosslinking, and therefore the degree of cure, is measured in a test sample of a cured polymer product prepared by a wet curing method. According to UL 2556, Wire and Cable Test Methods, Section 7.9, the test sample is subjected to a thermal creep test method at a certain load, Wt, and 200°C. Load Wt = CA * 200 kilopascals (kPa, 29.0 pounds-feet per square inch), where CA is the cross-sectional area of ​​a dog-bone sample cut from a pressed sheet prepared according to the sheet preparation method. Prepare three dog-bone samples / test materials. Make two marks on the sample at an original distance G separated from each other, where G = 25 + / - 2 mm. Place in the upper fixture of the thermal creep test assembly. Suspend a load of 0.2 megapascals (MPa) from the clamped sample. The test assembly with the dog bone specimen is heated in a preheated circulating air oven at 200°C + / - 2°C for 15 minutes and then the final length De of the specimen between the marks is measured while the load is still attached. The percent thermal creep elongation (HCE) is calculated according to Equation 1: HCE = [100*(De-G)] / G(1). The extension divided by the initial length gives a measure of the percent thermal creep. The lower the percent thermal creep, the lower the degree of elongation of the test specimen under load, and thus the greater the degree of crosslinking, and thus the greater the degree of cure. Lower thermal creep values ​​indicate a higher degree of crosslinking. Thermal creep measurements of cured specimens immersed in a 90°C ± 2°C water bath for 20 hours indicate the final degree of crosslinking in the cured product. The greater the final degree of crosslinking in the cured polymer product, the greater the amount of non-crosslinkable polymer or non-moisture-curable (e.g., may be only peroxide and / or light-curable) polymer (e.g., other than HSG-FP copolymer (e.g., polyethylene)) that can be incorporated into the moisture-curable polyethylene formulation and still achieve satisfactory hot creep properties of less than or equal to 175% for the cured polymer product after curing.

[0071] Wire coating preparation method: A Brinell 3 / 4 inch (1.91 cm) extruder was used with a variable speed drive, a 25:1 Maddock mixing head screw, a Brinell crosshead wire die, a laboratory water cooling tank with an air wipe, a laser micrometer and a variable speed wire puller, a temperature profile of 150°C (zone 1), 170°C (zone 2), 190°C (zone 3) and 195°C (head / die) and a 40 / 40 mesh screen package. The melt was extruded at a screw speed of 40 revolutions per minute (rpm) and a winding speed of about 2.4 meters (m) (8 feet) per minute, and a coating of the molten mixture was deposited on a 14 AWG solid copper wire (1.628 mm diameter; AMG is American Wire Gauge). The coating had a nominal wall thickness of 0.8 mm.

[0072] Coated Wire Curing Method: Cured wire samples prepared according to the wire coating preparation method were immersed in a water bath maintained at 95°C for different lengths of time to obtain cured insulated wire samples as reported later. A portion of the cured coating ("insulation") was peeled off from the copper by pulling it slightly to facilitate the removal of the insulation, and its thermal creep performance was measured. Thermal creep testing was performed on insulated samples without conductors in an oven set at 200°C at a stress of 0.2 MPa at the bottom of the sample to elongate the sample for 15 minutes. The results of the average elongation of three samples are reported (expressed as a percentage). For details, see Thermal Creep Test Method.

[0073] Moving Die Rheometer (MDR) Test Method (MDR: ML at 182°C (Nm), MDR: MH-ML at 182°C (Nm): ASTM D5289-12, Standard Test Method for Rubber Property—Vulcanization Using Rotorless Cure Meters. The torque of a 6 gram cold press test sample is measured using the following procedure. In a moving die rheometer (MDR) instrument MDR2000 (α Technology), the test sample obtained directly from the Brookfield mixing bowl is heated for 20 minutes at 182°C under 0.5 degree arc oscillation while monitoring the change in torque. The lowest torque value measured is expressed as "ML" in deciNewton-meters (dN-m). As curing or crosslinking progresses, the measured torque value increases, eventually reaching a maximum torque value. The maximum or highest torque value measured is expressed as "MH" in dN-m. All other things being equal, the higher the MH torque value, the greater the degree of crosslinking. All other things being equal, the greater the difference in MH-ML torque values, the greater the amount of crosslinking. The units of measurement are pound-inches (lb.-in.) and are converted to Newton-meters (Nm), where 1.00 lb.-in. = 0.113 Nm.

[0074] Polyolefin solid 1: density 0.92g / cm 3 , linear low density polyethylene (LLDPE) having a melt index (I2) of 0.65 g / 10 min. Used in the form of pellets.

[0075] Polyolefin solid 2: Reactor HSG-FP copolymer made by copolymerizing ethylene with vinyltrimethoxysilane (VTMS) at high pressure and temperature in the presence of an organic peroxide catalyst and in the absence of a metal-based catalyst. The HSG-FP copolymer has a trimethoxysilylethyl content of 1.5 wt%, a density of 0.92 g / cm 3 The melt index (I2) is 1.5 g / 10 min. It is used in the form of dry pellets.

[0076] Polyolefin solid 3: Reactor HSG-FP copolymer made by copolymerizing ethylene with 3-methacryloxypropyltrimethoxysilane (M3M) at high pressure and temperature in the presence of an organic peroxide catalyst and in the absence of a metal-based catalyst. The melt index (I2) of polyolefin solid 3 is 0.9 g / 10 min and the M3M content is 0.9 wt%. Used in the form of dry pellets.

[0077] Liquid Additive 1: Vinyltrimethoxysilane (VTMS), an alkenyl functional hydrolyzable silane comonomer, delivered as a neat liquid.

[0078] Liquid Additive 2: Dicumyl peroxide (DCP), an organic peroxide, delivered as a neat liquid.

[0079] Liquid Additive 3: Dibutyltin dilaurate (DBTDL), a moisture cure catalyst, was delivered as a neat liquid.

[0080] Liquid Additive 4: Octyltriethoxysilane (OTES), a scorch retarder, delivered as a neat liquid. Available as PROSIL 9202.

[0081] Particulate solid additive 1: natural (colorant-free) catalyst masterbatch containing 85 wt% of a 0.92 g / cm 3 and a linear low-density polyethylene (LLDPE) with a melt index (I2) of 0.65 g / 10 min, a 9wt% density of 0.92 g / cm 3 and a low density polyethylene (LDPE) having a melt index (I2) of 2 g / 10 min, 3.4 wt% solid antioxidant pentaerythritol tetrakis (3-(3,5-bis (1,1-dimethylethyl) -4-hydroxyphenyl) propionate and 2.6 wt% dibutyltin dilaurate. (Dried under vacuum at 60°C overnight before use.)

[0082] Particulate solid additive 2: Alumina trihydrate (ATH), an in situ water generator, delivered in pure solid form.

[0083] Comparative Example 1 (CE1): A homogeneous mixture was prepared by melt mixing its ingredients (polyolefin solid 1 and liquid additives 1 and 2 and particulate solid additive 1) in an extruder. Polyolefin solid 1 was preheated in a glass bottle at 70°C for one hour. Liquid additives 1 and 2 were added. Tumble mixing was continued for 10 minutes. The glass bottle with the mixture was left to stand overnight in an oven at room temperature for 16 to 20 hours to completely immerse the liquid additives 1 and 2 in the polyolefin solid 1. The resulting liquid additives 1 and 2-immersed polyolefin solid 1 was physically blended with the particulate solid additive 1 to obtain a heterogeneous mixture. A polyolefin solid 1 and a particulate solid additive 1 of a melted heterogeneous mixture are mixed and the heterogeneous mixture melt is mixed in a Brookfield 3 / 4 inch (1.91 cm) extruder having a variable speed drive, a 25:1 Maddock mixing head screw, a Brookfield crosshead wire die, a laboratory water cooling tank with an air wipe, a laser micrometer and a variable speed wire puller, a temperature profile of 150° C. (zone 1), 170° C. (zone 2), 190° C. (zone 3) and 195° C. (head / die) and a 40 / 40 mesh screen package to obtain a melt of the polyolefin solid additive 1, a melt of the particulate solid additive 1 and a melt-mixed homogeneous mixture of liquid additives 1 to 3.

[0084] Comparative Example 1A (CE1A). The melt-mixed homogeneous mixture of CE1 was extruded as a coating onto a 14 AWG solid copper wire to simulate the manufacture of a coated conductor, and the thermal creep properties of the coating were measured. The melt-mixed homogeneous mixture was extruded as a coating onto a wire according to the wire coating preparation method described above using the same extruder and extruder conditions as in CE1. The coating was cured to obtain the insulated wire of CE1A, and a portion of the insulation was stripped therefrom and its thermal creep properties were measured according to the coated wire curing method.

[0085] Inventive Example 1 (IE1): A homogenous mixture was prepared by sonicating its ingredients (Polyolefin Solid 1 and Liquid Additives 1 and 2 and Particulate Solid Additive 1) in a sonic mixer. 150 grams (g) of Polyolefin Solid 1, 2.41 grams of Liquid Additive 1 and 0.16 grams of Liquid Additive 2 were added to a glass bottle and the bottle contents were sonicated for 2 minutes at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a first homogenous mixture. 8 g of Particulate Solid Additive 1 was then added to form a second heterogeneous mixture. The second heterogeneous mixture was sonicated for 0.5 minutes to obtain a second homogeneous mixture.

[0086] Inventive Example 1A (IE1A): A sonic-mixed second homogenous mixture of IE1 was extruded as a coating onto a 14 AWG solid copper wire to simulate the manufacture of a coated conductor, and the thermal creep properties of the coating were measured. The second homogenous mixture of IE1 was added to a Brinell 3 / 4 inch (1.91 cm) extruder to melt polyolefin solid 1 and particulate solid additive 1 to obtain a second homogenous mixture in the form of a melt. The melt was extruded as a coating onto a wire according to the wire coating preparation method described above using the same extruder and extruder conditions as in CE1. The coating was cured to obtain an insulated wire of IE1A, and a portion of the insulation was stripped therefrom and its thermal creep properties were measured according to the coated wire curing method.

[0087] Table 1: Composition of Comparative Example 1 and Example 1 of the present invention and thermal creep properties of Comparative Example 1 and Example 1A of the present invention.

[0088]

[0089] In Table 1, the hot creep measurements taken after curing the mixture of CE1 and IE1 to obtain the insulated wires of CE1A and IE1A surprisingly show that the percent elongation of the cured samples prepared by curing the sonic mixed homogeneous mixture of the present invention for 0.5, 1 or 2 hours is advantageously lower than the percent elongation of the cured samples prepared by curing the comparative melt mixed homogeneous mixture for 0.5, 1 or 2 hours. That is, a greater degree of curing (cross-linking) is advantageously achieved earlier with the mixture of the present invention. However, the percent elongation of the cured sample prepared by curing the sonic mixed homogeneous mixture of the present invention for 6 hours is higher than the percent elongation of the cured sample prepared by curing the comparative melt mixed homogeneous mixture for 6 hours. The main value of the present invention is easier mixing, which is demonstrated by the foregoing.

[0090] Furthermore, the unaged and aged tensile strengths of the sonic-mixed homogenous mixture IE1 of the present invention are higher than those of the melt-mixed homogenous mixture CE1.

[0091] Comparative Example 2 (CE2): A homogenous mixture was made by immersing its melt-mixed components (polyolefin solid 2 and liquid additive 4). Polyolefin solid 2 was preheated in a glass bottle at 70°C for 30 minutes. Liquid additive 4 was added. Tumble mixing continued for 10 minutes. The glass bottle with the mixture was left standing in an oven overnight at room temperature for 16 to 20 hours to completely immerse the liquid additive 4 in the polyolefin solid 2.

[0092] Inventive Example 2 (IE2): A homogenous mixture was prepared by sonicating polyolefin solid 2, liquid additive 3 and particulate solid additive 2 in a sonic mixer. 160 g of polyolefin solid 2 and liquid additive 3 were added to a glass bottle to prepare a first heterogeneous mixture comprising polyolefin solid 2 and liquid additive 3; and the contents of the bottle were sonicated for 2 minutes at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a first homogenous mixture comprising polyolefin solid 2 and liquid additive 3. The particulate solid additive 2 was then added to the first homogenous mixture to obtain a second heterogeneous mixture comprising polyolefin solid 2, particulate solid additive 2 and liquid additive 3. The second heterogeneous mixture was sonicated for 2 minutes at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a second homogenous mixture comprising polyolefin solid 2, particulate solid additive 2 and liquid additive 3.

[0093] Inventive Example 3 (IE3): A homogenous mixture was prepared by sonicating polyolefin solid 2, liquid additives 3 and 4, and particulate solid additive 2 in a sonic mixer. 160 g of polyolefin solid 2 and liquid additive 4 were added to a glass bottle to prepare a first heterogeneous mixture comprising polyolefin solid 2 and liquid additive 4; and the contents of the bottle were sonicated for 2 minutes at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a first homogenous mixture comprising polyolefin solid 2 and liquid additive 4. The particulate solid additive 2 and liquid additive 3 were then added to the first homogenous mixture to obtain a second heterogeneous mixture comprising polyolefin solid 2, particulate solid additive 2, and liquid additives 3 and 4. The second heterogeneous mixture was sonicated for 2 minutes at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a second homogenous mixture comprising polyolefin solid 2, particulate solid additive 2, and liquid additives 3 and 4.

[0094] Inventive Example 4 (IE4): A homogenous mixture was prepared by sonicating polyolefin solid 3, liquid additive 3, and particulate solid additive 2 in a sonic mixer. The procedure of IE2 was repeated except that polyolefin solid 3 was substituted for polyolefin solid 2 by equal weight to prepare a first homogenous mixture comprising polyolefin solid 3 and liquid additive 3; a second heterogenous mixture comprising polyolefin solid 3, particulate solid additive 2, and liquid additive 3; and a third homogenous mixture comprising polyolefin solid 3, particulate solid additive 2, and liquid additive 3.

[0095] Inventive Example 5 (IE5): Particulate solid additive 2 and liquid additive 3 were added to the obtained liquid additive 4-immersed polyolefin solid 2 of CE2 to obtain a heterogeneous mixture. The heterogeneous mixture was sonicated using a RESODYN sonic mixer (LabRAM mixer) at 23° C. to 26° C. for 2 minutes to prepare a first homogeneous mixture of polyolefin solid 2, particulate solid additive 2 and liquid additives 3 and 4.

[0096] Table 2: Composition, visual observations and moving die rheometer (MDR) properties of Comparative Example 2 and Examples 2 to 5 of the present invention.

[0097]

[0098] In Table 2, the homogenous compositions of CE2, IE3, and IE5 contain a scorch retarder (OTES), while the homogenous compositions IE2 and IE4 do not contain a scorch retarder (OTES). In Table 2, the effectiveness of acoustic mixing in making homogenous compositions in IE2 to IE5 is similar to the immersion method of CE2, but the acoustic mixing method achieves homogeneity in substantially less time and at substantially lower temperatures. In addition, the acoustic mixing method is also effective for making a homogenous mixture in the form of dry pellets or powders.

[0099] Inventive Examples 6 to 11 (IE6 to IE11): A homogenous mixture was prepared by sonicating polyolefin solid 1, liquid additives 2 and 3, particulate solid additive 2, and optional liquid additive 1 in a sonic mixer. 160 g of polyolefin solid 1 and liquid additives 2 and 3, particulate solid additive 2, and optional liquid additive 1 were added to a glass bottle to prepare a heterogeneous mixture comprising polyolefin solid 1, liquid additives 2 and 3, particulate solid additive 2, and optional liquid additive 1; and the contents of the bottle were sonicated for 1 minute at 23° C. to 26° C. using a RESODYN sonic mixer (LabRAM mixer) to prepare a homogenous mixture comprising polyolefin solid 1, liquid additives 2 and 3, particulate solid additive 2, and optional liquid additive 1.

[0100] Table 3: Composition, visual observations and moving die rheometer (MDR) properties of Examples 6 to 11 of the present invention.

[0101]

[0102] In Table 3, the results of testing homogenous mixtures of IE6 to IE11 in the MDR at 160°C for 60 minutes, followed by an additional 30 minutes at 200°C are shown. The total increase in MDR torque ("differential torque") over the entire 90 minute period was calculated, which serves as an indicator of the degree of crosslinking due to thermal decomposition of peroxide (causing peroxide crosslinking via carbon-carbon coupling) and / or decomposition of the particulate solid additive 2 (ATH), thereby causing in situ water generation and thus silane crosslinking via hydrolysis and condensation reactions when the liquid additive 1 (VTMS) is grafted to the polyethylene. At 0.05 wt% liquid additive 2 (DCP) loading, there is little or no difference in differential torque in the presence and absence of liquid additive 1 (VTMS). As the amount of liquid additive 2 (DCP) increases to 0.2 wt%, it is observed that the homogenous mixture containing liquid additive 1 (VTMS) exhibits progressively larger differential torque values ​​compared to the corresponding formulation without liquid additive 1 (VTMS). Without being bound by theory, it is believed that the differential torque values ​​observed in the absence of liquid additive 1 (VTMS) are attributed only to the carbon-carbon bond formation / crosslinking promoted by peroxide (liquid additive 2 (DCP)), while the differential torque values ​​observed in the presence of liquid additive 1 (VTMS) are attributed to the combination of carbon-carbon crosslinking promoted by peroxide (liquid additive 2 (DCP)) and silane crosslinking promoted by moisture. At any given peroxide (liquid additive 2 (DCP)) loading, the difference between the line graphs of differential torque relative to the MDR time period line reflects the additional contribution of silane crosslinking relative to peroxide crosslinking only. These data show that in a homogeneous mixture, the grafting efficiency of liquid additive 1 (VTMS) increases with the increase of the amount of liquid additive 2 (DCP). After these MDR evaluations, the resulting material is between thermoplastic (at low differential torque values) and thermosetting (at higher differential torque values) range.

Claims

1. A method for forming a homogeneous mixture of a polyolefin solid and a liquid additive without melting the polyolefin solid during said forming, said method comprising applying acoustic energy to a first heterogeneous mixture comprising at least one liquid additive and (A) a polyolefin solid at a frequency of 20 to 100 Hz for a certain period of time and at an acoustic intensity effective to substantially intermix the at least one liquid additive and the polyolefin solid; while maintaining the temperature of the first heterogeneous mixture above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming a first homogeneous mixture comprising the polyolefin solid and the at least one liquid additive without melting the polyolefin solid, The liquid additive is added to the polyolefin solid in pure liquid form and the heterogeneous mixture does not contain any liquid solvent, in, The polyolefin of the polyolefin solid is: polyethylene homopolymer; ethylene / α-olefin copolymer; hydrolyzable silane functional polyethylene copolymer; ethylene / unsaturated carboxylic acid ester copolymer; or a blend of any two or more thereof.

2. The method of claim 1, wherein the applying step is characterized by any one of the following features (i) to (v): (i) the frequency is 50 to 70 Hz; (ii) the time period is 0.5 minutes to 4 hours; (iii) both (i) and (ii); (iv) maintaining the temperature of the first heterogeneous mixture below the melting temperature of the polyolefin solid comprises maintaining the temperature of the first heterogeneous mixture at 10°C to 109°C; and (v) any one of (i) to (iii) and both (iv).

3. The method of claim 1, wherein the polyolefin solids of the first heterogeneous mixture are characterized by a physical form of powder, granules or pellets and by a melting temperature of 61°C to 180°C; and the at least one liquid additive of the first heterogeneous mixture is characterized by a freezing point below 20°C, or by a melting point of 20°C to 99°C; and during the applying step, the first heterogeneous mixture is maintained at a temperature greater than the freezing point or melting point of the at least one liquid additive and less than 110°C.

4. The method of claim 2, wherein the polyolefin solids of the first heterogeneous mixture are characterized by a physical form of a powder, granules or pellets and by a melting temperature of 61°C to 180°C; and the at least one liquid additive of the first heterogeneous mixture is characterized by a freezing point below 20°C, or by a melting point of 20°C to 99°C; and during the applying step, the first heterogeneous mixture is maintained at a temperature greater than the freezing point or melting point of the at least one liquid additive and less than 110°C.

5. The method according to any one of claims 1 to 4, wherein the at least one liquid additive is additive (B) liq to (I) liq Any one or more of: (B) liq , liquid silanol condensation catalyst; (C) liq , liquid antioxidant; (D) liq , liquid colorant; (E) liq , liquid anti-scorch agent; (F) liq , liquid stabilizers for stabilizing the homogeneous mixture against the effects of ultraviolet rays (UV stabilizers); (G) liq , liquid processing aid; (H) liq , a liquid flame retardant; and (I) liq , which is not a liquid polymer of (A).

6. The method of any one of claims 1 to 4, wherein the first heterogeneous mixture further comprises at least one particulate solid additive different from the polyolefin solids, and the first homogenous mixture further comprises the at least one particulate solid additive.

7. The method according to any one of claims 1 to 4, further comprising, before the applying step, forming the first heterogeneous mixture by a contacting step (i) or (ii): (i) contacting the polyolefin solid with at least one liquid additive to form the first heterogeneous mixture; or (ii) contacting the polyolefin solid with a lower melting point solid additive having a melting point of 25°C to 110°C to form a heterogeneous solid premixture, and melting the lower melting point solid additive without melting the polyolefin solid to form the first heterogeneous mixture.

8. The method of any one of claims 1 to 4, further comprising the steps of: contacting the first homogenous mixture with at least one particulate solid additive different from the polyolefin solid to form a second heterogeneous mixture comprising the first homogenous mixture and the at least one particulate solid additive; and subsequently applying sonic energy at a frequency of 20 to 100 Hz and at an intensity effective to substantially intermix the second heterogeneous mixture while maintaining the temperature of the second heterogeneous mixture above the freezing point of the at least one liquid additive and below the melting temperature of the polyolefin solid, thereby forming a second homogenous mixture without melting the polyolefin polymer solid during the forming step, the second homogenous mixture comprising the polyolefin solid, the at least one liquid additive and the at least one particulate solid additive.

9. The method according to any one of claims 1 to 4, further comprising the steps of: melting the polyolefin solid of the homogeneous mixture to form a molten mixture; shaping the molten mixture to obtain a shaped molten mixture; and cooling the shaped molten mixture to obtain a shaped solid.

10. The method of claim 9, wherein the forming step comprises extruding the molten mixture as a coating onto a conductive core, and solidifying the coating to produce a coated conductor comprising the conductive core and a coating-shaped solid at least partially covering the conductive core.

11. The method of claim 9, further comprising curing the shaped solid polyolefin to obtain a shaped cured product.

12. The method of claim 10, further comprising curing the shaped solid polyolefin to obtain a shaped cured product.

Citation Information

Patent Citations

  • Moisture-curable polymeric compositions having halogenated polymers and metal mercaptides

    US10119015B2

  • Pad for herbal medicine in which release of medicinal ingredient can be controlled, and manufacturing method thereof

    US20120209056A1

  • Apparatus and method for resonant-vibratory mixing

    US7188993B1

  • Thermally conductive grease and methods and devices in which said grease is used

    US7695817B2

  • Solvent-free emulsion process

    US8124309B2